The Feasibility Analysis and Technical Efficiency of Seed Water Spinach Farming in Sumurcinde Village Soko District Tuban Regency - Isti Ningrum Murdiyanti; Darsan Darsan; Fina Sulistiya Ningsih (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2023)
Seed water-spinach cultivation is one of the promising agribusiness enterprises for farmers. Farmer opts for this business because the selling price of water spinach is high enough. The lack of information regarding technical efficiency and practicality in their hometown is the crucial reason for this research. This study aimed to determine seed water-spinach cultivation's feasibility and technical efficiency at Sumurcinde village in the Soko District of Tuban Regency. This study was conducted from December until January 2023 with samples of 67 farmers. The analysis used is properness analysis by counting the charges, Revenue, income, R/C ratio, B/C ratio, and BEP and technical efficiency analysis by using software frontier 4.1 employing y variable such as production result and x variables such as land area, seed, labor, phonska fertilizer, urea fertilizer, power grow fertilizer and pesticide. The outcome shows that the average expense spent by farmers is IDR3.028.285, the revenue average is IDR 13.281.731, and the income average is IDR10.252.715. The value of the R/C ratio is 4,39 >1, while the number of B/C ratios is 3,39 >1. Therefore, it can be concluded that the farming business of water-spinach seed is worth working on. The BEP value of production volume is 159.38 kilograms, and the BEP value in Indonesian rupiahs is 4.33,31. The source water-spinach business at Sumurcinde village has been efficient and profitable because the volume and selling price are higher than the BEP value. The average farmers have achieved high technical efficiency. This technical efficiency mean is 0,89 with a minimum value of 0,56 and a maximal value of 0,97.